ESSENTIAL TERMS OF THE TECHNOLOGY TRANSFER AGREEMENT:PROBLEMS AND SOLUTIONS WITHIN THE CONTEXT OF INTERNATIONALIZATION (Вісник: Міжнародні відносини, 2021)
The article is devoted to define the legal nature of a technology transfer agreement, its content, and constituent elements. The subject matter of thetechnology transfer agreement is defined. The necessity of specifying the list of objects of intellectual property rights that can be the object of technologytransfer is noted. It is determined that together with the objects of intellectual property rights, the objects of technology also include scientific andscientific-applied results of know-how, which reflect a list, terms, procedure, and sequence of operations, the process of production and/or sale and storage of products. This leads to limitations in the possibilities of applying the provisions of Chapter 75 of the Civil Code of Ukraine to such agreements.The conclusion about the redundancy of the list of mandatory provisions of the technology transfer agreement, as well as the risks, the occurrence ofwhich may be a consequence of the lack of reflection in the technology transfer agreement of each of these mandatory provisions (such an agreement could potentially be considered as voidable). It is determined that specific essential terms of the technology transfer agreement specified by law should be the subject of separate agreements and not be part of the transfer of property rights to the technology or its components.From the standpoint of legal doctrine, the available legal approaches to understanding the essential terms of technology transfer agreements areanalyzed, and the reduction of the list of mandatory provisions of technology transfer agreements by making amendments to the legislation of Ukraineis substantiated.
Keywords: technology transfer, technology, patent, contract, essential terms